Structural and Functional Coupling of Calcium-Activated BK Channels and Calcium-Permeable Channels Within Nanodomain Signaling Complexes - Shah, Kunal R.; Guan, Xin; Yan, Jiusheng (Frontiers in Physiology, 2022)
Biochemical and functional studies of ion channels have shown that many of these integral membrane proteins form macromolecular signaling complexes by physically associating with many other proteins. These macromolecular signaling complexes ensure specificity and proper rates of signal transduction. The large-conductance, Ca2+-activated K+ (BK) channel is dually activated by membrane depolarization and increases in intracellular free Ca2+ ([Ca2+]i). The activation of BK channels results in a large K+ efflux and, consequently, rapid membrane repolarization and closing of the voltage-dependent Ca2+-permeable channels to limit further increases in [Ca2+]i. Therefore, BK channel-mediated K+ signaling is a negative feedback regulator of both membrane potential and [Ca2+]i and plays important roles in many physiological processes and diseases. However, the BK channel formed by the pore-forming and voltage- and Ca2+-sensing  subunit alone requires high [Ca2+]i levels for channel activation under physiological voltage conditions. Thus, most native BK channels are believed to co-localize with Ca2+-permeable channels within nanodomains (a few tens of nanometers in distance) to detect high levels of [Ca2+]i around the open pores of Ca2+-permeable channels. Over the last two decades, advancement in research on the BK channel’s coupling with Ca2+-permeable channels including recent reports involving NMDA receptors demonstrate exemplary models of nanodomain structural and functional coupling among ion channels for efficient signal transduction and negative feedback regulation. We hereby review our current understanding regarding the structural and functional coupling of BK channels with different Ca2+-permeable channels.